2016
DOI: 10.3233/jad-160210
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks Link One-Carbon Metabolism to Gene-Promoter Methylation in Alzheimer’s Disease

Abstract: The present pilot study suggests that promoter methylation levels of the studied genes are linked to circulating levels of folates, hcy, and vitamin B12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 23 publications
(39 reference statements)
4
27
0
Order By: Relevance
“…Plasma Hcy, serum folate, and vitamin B12 levels were available from 158 individuals, and their average values are shown in Table 1. The promoter methylation levels of the DNMT1 gene ranged from 0% to 15% in the study population ( Figure 2), with an average value of 2.2% (Table 1), which is in agreement with previous investigations in other cohorts [14,20,21]. The genotype distribution of the investigated polymorphisms is shown in Table 2.…”
Section: Distribution Of the Investigated Variables In The Study Popusupporting
confidence: 89%
See 1 more Smart Citation
“…Plasma Hcy, serum folate, and vitamin B12 levels were available from 158 individuals, and their average values are shown in Table 1. The promoter methylation levels of the DNMT1 gene ranged from 0% to 15% in the study population ( Figure 2), with an average value of 2.2% (Table 1), which is in agreement with previous investigations in other cohorts [14,20,21]. The genotype distribution of the investigated polymorphisms is shown in Table 2.…”
Section: Distribution Of the Investigated Variables In The Study Popusupporting
confidence: 89%
“…Little is still known concerning genetic, dietary, or environmental factors linked to changes in DNMT1 methylation levels. In this regard, a previous investigation in peripheral blood DNA samples of Alzheimer's disease (AD) individuals suggested that the promoter methylation levels of several genes, including DNMT1, could be linked to circulating markers of folate metabolism, and particularly to plasma homocysteine (Hcy) levels [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, as far as MTHFR promoter methylation in the blood is concerned, it should be noted that rather than being a specific marker of a given disease, it could represent a more general biomarker of increased genomic instability. For example, some studies suggest a correlation between hyperhomocysteinemia and MTHFR promoter methylation [26]; others have linked MTHFR promoter methylation in blood cells with markers of chromosome damage, such as an increased frequency of micronuclei [27] or alterations of LINE-1 methylation and stability [15], and there is also indication that MTHFR promoter methylation in blood DNA might reflect dietary B-group vitamin deficiency [18,30] or environmental exposure to cancerous agents, such as those deriving from tobacco smoking [15]. Collectively, those studies suggest that increased MTHFR promoter methylation in blood cells might be a more general marker of impaired one-carbon metabolism and genome instability, rather than a specific disease biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Grossi et al [17] used artificial neural network analysis to illustrate how low cobalamin; low folate and high Hcy are linked to AD. Low PSEN1 methylation was linked to low folate levels and low promoter methylation of BACE1 and DNMT genes.…”
Section: Gene Regulation Is Achieved By 5mc Silencing Gene Expressionmentioning
confidence: 99%